Arise, Africa! roar, China! : Black and Chinese citizens of the world in the twentieth century - Gao, Yunxiang (John Hope Franklin series in African American history and culture., 2021)
"This book explores the close relationships between three of the most famous twentieth-century African Americans, W.E.B. Du Bois, Paul Robeson, and Langston Hughes, and their little-known Chinese allies during World War II and the Cold War-journalist, musician, and Christian activist Liu Liangmo, and Sino-Caribbean dancer-choreographer Sylvia Si-lan Chen. Charting a new path in the study of Sino-American relations, Gao Yunxiang foregrounds African Americans, combining the study of Black internationalism and the experiences of Chinese Americans with a trans-Pacific narrative and an understanding of the global remaking of China's modern popular culture and politics. Gao reveals earlier and more widespread interactions between Chinese and African American leftists than accounts of the familiar alliance between the Black radicals and the Maoist Chinese would have us believe. The book's multilingual approach draws from massive yet rarely used archival streams in China and in Chinatowns and elsewhere in the United States. These materials allow Gao to retell the well-known stories of Du Bois, Robeson, and Hughes alongside the sagas of Liu and Chen in a work that will transform and redefine Afro-Asia studies"--